LCT-3d Induces Oxidative Stress-Mediated Apoptosis by Upregulating Death Receptor 5 in Gastric Cancer Cells - Wang, Menglin; Wu, Xinxin; Yu, Lu; Hu, Zi-yun; Li, Xiaobo; Meng, Xia; Lv, Chun-tao; Kim, Gi-Young; Choi, Yung Hyun; Wang, Zhenya; Xu, Hai-Wei; Jin, Cheng-Yun (Frontiers in Oncology, 2021)
Gastric cancer is a global health problem. In this study, we investigate the role of a novel Indole derivative, named LCT-3d, in inhibiting the growth of gastric cancer cells. LCT-3d modulated the mitochondrial-related proteins and Cleaved-Caspases 3/9, to induce cell apoptosis. The up-regulation of DR5 in MGC803 cells was observed with LCT-3d treatment. Knockdown of DR5 on MGC803 cells partially reversed the LCT-3d-induced mitochondrial apoptosis. The level of ROS in MGC803 cells was increased with LCT-3d treatment and could be blocked with the pretreatment of NAC. The results demonstrate that the elevating ROS can up-regulate the expression of DR5, resulting in apoptosis via mitochondrial pathway. Although the Nrf2 pathway served an important role in protecting gastric cancer cells against the injury of ROS, it can`t reverse LCT-3d-induced cell apoptosis. Taken together, our study shows that LCT-3d induces apoptosis via DR5-mediated mitochondrial apoptotic pathway in gastric cancer cells. LCT-3d could be a novel lead compound for development of anti-cancer activity in gastric cancer.